Turning on the townships: a study of discourses of financial inclusion in South Africa - Kruger, Graunt (My University, 2016)
Financial inclusion is promoted as an important economic development program to solve the lack of access to formal financial services for billions of people around the world. The concept “financial inclusion” has entered mainstream business and development discourses as an all-encompassing term for innovation in financial services for the poor. South African policymakers and financial service providers have embraced this approach to address some of the country’s political, social and economic imbalances. A number of examples are held up as successes of financial inclusion such as India’s “Jan Dhan Yojana” initiative. The program, launched in August 2014, signed up 75 million people to new bank accounts in under three months. South African policymakers and financial service providers have also embraced financial inclusion to address the country’s political, social and economic imbalances. Several consequences challenge this optimistic view. The first issue is the high level of dormancy across various services. India’s account has up to 75% dormancy, much like South Africa’s Mzansi account launched expressly for financial inclusion in 2005. It was abandoned by 2012 due to lack of use. The second major issue is adverse inclusion that arises after people are “financially included” and they end up worse off than before. In August 2014 African Bank, the largest lender to low-income individuals in South Africa, failed because it had issued loans to customers who eventually could not afford to repay them. Despite these issues, the focus of financial inclusion remains on targets of density, penetration and geographic access as measured in the World Bank’s Findex, a global financial inclusion database. Practitioners and researchers tend to be concerned with how people as borrowers, savers, bank account users and mobile phone users access and use financial services. Yet an unexplored issue is how these subject positions came to be, how they are maintained and the specific rationalities that accompany them. Following Foucault, this study is an attempt to understand how the concept of financial inclusion has functioned in our society to create human beings as subjects. This is a seven-year genealogical research project of South Africa’s national financial inclusion effort. Over this period, three discourse clusters were identified and analysed. The first cluster consists of 12 texts produced by a range of public, private and civil society institutions. The second cluster of academic discourses on financial inclusion consists of 3 83 peer-reviewed journal articles published between 2009 and 2013. The third cluster is a collection of texts from local sources in two townships produced by those individuals who are often the subjects in the other discourse clusters. The analysis reveals dominant modes of objectification in each cluster and the synthesis enables the search for evidence of a regime of truth on financial inclusion. Evidence indicates that dominant discourses of financial inclusion, irrespective of origin, limit subjects to existing practices of money management. Therefore, despite claims of the sweeping changes that can result from financial inclusion, this study argues that this form of development discourse perpetuates existing concentrations of wealth. Counter-narratives that link financial inclusion and asset building offer an important break in this dominance
thesis submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, Johannesburg, South Africa in fulfilment of the requirements for the degree of Doctor of Philosophy (PhD) Johannesburg, August 2015
Keywords: Poor--Finance; Microfinance--South Africa; Banks and banking, Mobile--South Africa